Synergy Strategies Between UIN Raden Intan Lampung and MSMEs: A Sustainable Business Model - Dermawan, Oki (Equator Journal of Management and Entrepreneurship (EJME), 2026)
The collaboration between UIN Raden Intan Lampung (UIN RIL) and Micro, Small, and Medium Enterprises (MSMEs) aims to foster the development of sustainable business models through various initiatives, such as halal certification assistance, entrepreneurship training, and the rental of campus facilities. This article explores how this collaboration significantly supports the enhancement of MSME competitiveness, innovation, and sustainability. Through the cafeteria rental initiative, UIN RIL provides MSMEs with stable market access, while entrepreneurship training enhances the managerial capacity and adaptability of MSME owners. Additionally, halal certification expands MSMEs' market access both locally and internationally, improving product quality and consumer trust. However, challenges in operational management and low participation in training programs may hinder the long-term success of this collaboration. The article concludes that, for long-term sustainability, both UIN RIL and MSMEs must continue to innovate and strengthen their collaboration by providing better resources and improving MSME engagement in available programs. Recommendations for UIN RIL, MSMEs, and researchers include enhancing strategic planning, actively participating in training programs, and conducting further studies on the long-term impacts of this collaboration on local economies and MSME sustainability.